The Pengaruh Kualitas Layanan, Kualitas Produk dan Harga terhadap Kepuasan Pelanggan pada Toko Bangunan Ahsan Jaya Wringinanom Gresik - Ismanu, Ahmad; Setiawan, Erry; Cahyani, Diah; Nuraeni, Eny (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
The purpose of this study is to determine: 1) The partial effect of service quality on customer satisfaction; 2) The partial effect of product quality on customer satisfaction; 3) The partial effect of price on customer satisfaction; 4) The simultaneous effect of service quality, product quality, and price on customer satisfaction. The population in this study consists of all customers of Ahsan Jaya Building Store. Sample determination using non-probability sampling techniques with the Slovin formula yielded 60 respondents, and data distribution was conducted using accidental sampling. Data were analyzed using multiple linear regression, with hypothesis testing conducted partially using the t-test, while simultaneous hypothesis testing was conducted using the F-test. The research results indicate: 1) Service quality partially influences customer satisfaction; 2) Product quality partially influences customer satisfaction; 3) Price partially influences customer satisfaction; 4) Service quality, product quality, and price simultaneously influence customer satisfaction.